1992
DOI: 10.1016/0378-1097(92)90341-k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a lipoamide dehydrogenase gene as second locus affected in poly(3-hydroxybutyric acid)-leaky mutants of Alcaligenes eutrophus

Abstract: From a genomic library of Alcaligenes eutrophus strain H16 in the broad-host range cosmid pVK100 a 6300-bp EcoRI-fragment was cloned, which restored the wild-type phenotype in transposon-induced poly(3-hydroxybutyric acid)-leaky mutants, derived from A. eutrophus. Nucleotide sequence analysis of the region adjacent to the transposon insertion revealed an open reading frame which complied with all criteria for a coding region. This region was referred to as phbL, and the deduced amino acid sequence from this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…The in silico analysis also confirmed the presence of a genomic EcoRI fragment comprising all three genes of the PDHC, in agreement with the 6.3-kbp EcoRI fragment, which restored the wild-type phenotype in the PHB-leaky Tn5 mutant (46).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The in silico analysis also confirmed the presence of a genomic EcoRI fragment comprising all three genes of the PDHC, in agreement with the 6.3-kbp EcoRI fragment, which restored the wild-type phenotype in the PHB-leaky Tn5 mutant (46).…”
Section: Resultssupporting
confidence: 73%
“…The published data for the PHB-leaky Tn5 mutants exhibiting a reduced PHB accumulation rate (21,46) were verified and completed. Our investigations revealed that mutants H1474 and H1479 are most probably siblings of mutant H1482 because the Tn5 insertions had occurred at identical positions.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations